2005
DOI: 10.2224/sbp.2005.33.4.341
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Interplay of Student Motivation and Cognition in the College of Education Students at Kuwait University

Abstract: An everlasting controversial issue in is the problem of teaching students to become initiative-motivated, and self-regulating learners. This study focuses on the interactive relationships between students' motivation and cognition in the College of Education students at Kuwait University ‐ more specifically, the relationships between students' motivational orientation and their use of cognitive learning strategies as well as their metacognitive and effort management strategies (cf. Pintrich, 1988; Pintrich, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Results of many studies show that motivational beliefs significantly affect the use of metacognitive strategies employed by students (Al-Ansari, 2005;Dembo & Eaton, 2000;Neber & Schommer-Aikins, 2002;Pintrich & De Groot, 1990;ShuShen, 2002;Tung-hsien, 2004;Valle et al, 2003). These studies mainly focus on three general types of motivational beliefs, including expectancy (self-efficacy and control), task value, and goal orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Results of many studies show that motivational beliefs significantly affect the use of metacognitive strategies employed by students (Al-Ansari, 2005;Dembo & Eaton, 2000;Neber & Schommer-Aikins, 2002;Pintrich & De Groot, 1990;ShuShen, 2002;Tung-hsien, 2004;Valle et al, 2003). These studies mainly focus on three general types of motivational beliefs, including expectancy (self-efficacy and control), task value, and goal orientations.…”
Section: Introductionmentioning
confidence: 99%
“…Students with higher levels of intrinsic motivation to academic achievement are more likely to attain meaningful understanding. In fact, educational research has long since shown that there is a positive relationship between intrinsic motivation and the use of learning strategies that lead to meaningful understanding (Al-Ansari, 2005;Meece, Blumenfeld, & Hoyle, 1988;Neber & Schommer-Aikins, 2002;Pintich & DeGroot, 1990;Tung-hsien, 2004;Valle et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Just as this pathway is associated with a very disciplined approach, Entwistle and Ramsden's (1983) 'strategic approach' is negatively correlated with 'disorganised studying'. Although the evidence suggests that these students tend to be academically successful (Al-Ansari, 2005), there are some issues that need consideration. These students are careful to stay within the square.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between learning performance and motivation was established in the 1970s by the work of Biggs (1976Biggs ( , 1987 and Marton and Säljö (1976a,b). Other studies have looked at self efficacy (Anderman & Midgley, 1992;Bandura, 1993), expectancy and task value (Al-Ansari, 2005). Although measuring motivation in different ways, these studies agree that students high in motivation show higher levels of persistence and more directed effort.…”
Section: Motivationmentioning
confidence: 97%
See 1 more Smart Citation